2018
DOI: 10.3389/fimmu.2018.00820
|View full text |Cite
|
Sign up to set email alerts
|

CD22-Binding Synthetic Sialosides Regulate B Lymphocyte Proliferation Through CD22 Ligand-Dependent and Independent Pathways, and Enhance Antibody Production in Mice

Abstract: Sialic acid-binding immunoglobulin-like lectins (Siglecs) are expressed in various immune cells and most of them carry signaling functions. High-affinity synthetic sialoside ligands have been developed for various Siglecs. Therapeutic potentials of the nanoparticles and compounds that contain multiple numbers of these sialosides and other reagents such as toxins and antigens have been demonstrated. However, whether immune responses can be regulated by monomeric sialoside ligands has not yet been known. CD22 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 74 publications
1
19
0
1
Order By: Relevance
“…Additional evidence for CD22 being largely maintained away from the BCR comes from studies that force CD22 with the BCR, showing how profoundly this can inhibit BCR signaling relative to the modest difference in BCR signaling comparing WT to CD22 −/− B cells. A recent study using a nanomolar affinity soluble CD22 ligand also reported that this compound was capable of causing hypo-responsiveness of B cells in an St6gal1-dependent manner, which is consistent with this model [82]. Therefore, pharmacological, enzymatic, and genetic approaches to ablate CD22 ligands on the cell surface all demonstrate the same phenomenon, which is that they increase association of CD22 with the BCR, leading to hypo-responsive BCR signaling [Fig.…”
Section: Roles Of Glycan Ligands In Controlling Cd22 As a Bcr Inhibitsupporting
confidence: 68%
See 1 more Smart Citation
“…Additional evidence for CD22 being largely maintained away from the BCR comes from studies that force CD22 with the BCR, showing how profoundly this can inhibit BCR signaling relative to the modest difference in BCR signaling comparing WT to CD22 −/− B cells. A recent study using a nanomolar affinity soluble CD22 ligand also reported that this compound was capable of causing hypo-responsiveness of B cells in an St6gal1-dependent manner, which is consistent with this model [82]. Therefore, pharmacological, enzymatic, and genetic approaches to ablate CD22 ligands on the cell surface all demonstrate the same phenomenon, which is that they increase association of CD22 with the BCR, leading to hypo-responsive BCR signaling [Fig.…”
Section: Roles Of Glycan Ligands In Controlling Cd22 As a Bcr Inhibitsupporting
confidence: 68%
“…Earlier studies from CD22 −/− mice revealed an altered response in B cells following stimulation with a variety of TLR ligands [91], where CD22 appears to act as a negative regulator. More detailed analysis of WT versus CD22 −/− B cell responses to a variety of TLR ligands have solidified these findings [82], [111]. It is intriguing that up to a 5-10-fold increase in responsiveness to TLR ligands in CD22 −/− B cells is significantly more than the 50% increase in BCR stimulation.…”
Section: Beyond Regulation Of the Bcr: Other Roles For Cd22 In Contromentioning
confidence: 90%
“…Examples of such glycan-containing molecules include bacterial lipopolysaccharides, peptidoglycans, teichoic acids, capsular polysaccharides and fungal mannans. The recognition of these glycosylated microbial patterns by the immune system has been exploited for the development of vaccines 45,46 ; pneumococcal vaccines, for example, are formulated using a mixture of capsular polysaccharides 47 . The recent progress in H IV-1 vaccine development has also been driven by a better understanding of the HIV-1 envelope (Env) glycoprotein and the effects of its glycan composition on immune responses and immune evasion 4853 .…”
Section: Glycans In Immunity and Inflammationmentioning
confidence: 99%
“…Thus, CD22 normally may play a role in the direct inhibition of TLR signaling in B cells. The natural ligands for CD22 apparently do not play a direct role in regulating proliferative responses to TLR agonists since CD22 ligand-deficient ST6Gal1 −/− B cells have normal responses to LPS and CpG ( 40 ). CD22 is an endocytic receptor that recycles between the cell surface and the endosomes, where endosomal TLRs resides ( 41 ).…”
Section: Role Of Cd22 In Response To Antigens and Pathogenic Productsmentioning
confidence: 99%